Highly Pathogenic Avian Influenza H5N8 Clade 2.3.4.4b in Germany in 2016/2017 - Globig, Anja; Staubach, Christoph; Sauter-Louis, Carola; Dietze, Klaas; Homeier-Bachmann, Timo; Probst, Carolina; Gethmann, Jörn; Depner, Klaus R.; Grund, Christian; Harder, Timm C.; Starick, Elke; Pohlmann, Anne; et al. (Frontiers in Veterinary Science, 2018)
Here, we report on the occurrence of HPAI H5Nx clade 2.3.4.4b in Germany. Between 8 November 2016 and 30 September 2017, more than 1,150 cases of highly pathogenic avian influenza (HPAI) H5Nx clade 2.3.4.4b in wild birds and 107 outbreaks in birds kept in captivity (92 poultry holdings and 15 zoos/animal parks) were reported in Germany. This HPAI epidemic is the most severe recorded in Germany so far. The viruses were apparently introduced by migratory birds, sparking an epidemic among wild birds across Germany with occasional incursions into poultry holdings, zoos and animal parks, which were usually rapidly detected and controlled by stamping out. HPAI viruses (mainly subtype H5N8, in a few cases also H5N5) were found in dead wild birds of at least 53 species. The affected wild birds were water birds (including gulls, storks, herons and cormorants) and scavenging birds (birds of prey, owls and crows). In many cases, substantial gaps in farm biosecurity may have eased virus entry into the holdings. In a second wave of the epidemic starting from February 2017, there was epidemiological and molecular evidence for virus transmission of the infections between commercial turkey holdings in an area of high poultry density, which caused approximately 25 percent of the total number of outbreaks in poultry. Biosecurity measures in poultry holdings should be adapted. This includes, inter alia, wearing of stable specific protective clothing and footwear, cleaning and disinfection of equipment that has been in contact with birds and prevention of contacts between poultry and wild water birds.